1990
DOI: 10.1111/j.1471-0307.1990.tb02457.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydration related properties of protein isolates prepared from heated milks

Abstract: The hydration related properties of sodium casemate, conventional casein‐whey protein co‐precipitate preparedfrom milk heatedat 90°C × 15 min at pH 6.6 and milk protein isolates prepared from milk heated at 90°C × 15 min at pH 7.5 or at 60°C × 3 min at pH 10.0 were determined. Conventional acid‐precipitated casein and the acid‐precipitated protein isolates preparedfrom milks heated at pH >7.0 had similar solubilities and reconstitution properties which were better than those of a conventional co‐precipitate. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Protein isolation by acid precipitation of milk after heating at alkaline pH values offers advantages over other methods used for milk protein product manufacture. There is an increase in protein recovery compared to conventional acid casein manufacturing processes, and solubilities of the protein isolates are better than those of conventional co-precipitates (Grufferty & Mulvihill, 1987, 1990. The protein isolates have time dependent surface activities at the air-water interface similar to sodium caseinate and conventional co-precipitates, emulsifying capacities and emulsion stabilizing abilities similar to conventional co-precipitates but better than sodium caseinate, foam capacities less than sodium caseinate and better than conventional co-precipitates but foam stabilizing abilities better than sodium caseinate but less than conventional co-precipitates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein isolation by acid precipitation of milk after heating at alkaline pH values offers advantages over other methods used for milk protein product manufacture. There is an increase in protein recovery compared to conventional acid casein manufacturing processes, and solubilities of the protein isolates are better than those of conventional co-precipitates (Grufferty & Mulvihill, 1987, 1990. The protein isolates have time dependent surface activities at the air-water interface similar to sodium caseinate and conventional co-precipitates, emulsifying capacities and emulsion stabilizing abilities similar to conventional co-precipitates but better than sodium caseinate, foam capacities less than sodium caseinate and better than conventional co-precipitates but foam stabilizing abilities better than sodium caseinate but less than conventional co-precipitates.…”
Section: Discussionmentioning
confidence: 99%
“…44, No. I, February 1991 Mulvihill, 1990). When units of surface active protein transfer from the bulk phase to the fat interface it might be expected that the concentration of protein at the interface would be higher for more aggregated proteins than for less aggregated proteins and subsequently the greater protein load for the former type of protein.…”
Section: Journal Of the Society Of Dairymentioning
confidence: 99%
See 1 more Smart Citation
“…This method has been applied by Connolly [8] to aggregate and isolate proteins in mixtures of milk, whey and/ or soy milk at temperatures below 70°C. Combination of heat treatment and alkaline pH has also been applied to the manufacture of milk protein isolates (MPI), resulting in increased protein yield, increased rehydration properties and higher viscosity of the reconstituted powder in particular cases [7,16,17]. Grufferty and Mulvihill [16] have for instance obtained MPI from milk heated at pH 10 and 60°C for 3 min whose protein yield competed with those obtained at neutral or mildly alkaline pH on heating at 90-95 °C for 15 min, and showed that these Acid gelation of milk heated at alkaline pH 121 results depended on the formation of disulfide aggregates of κ-casein and whey proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In some of these studies, recovery of the protein fraction was performed using acidification to pH 4.6 [16,17]. The disulfide aggregates obtained in strong alkaline and mild heat-treatment conditions therefore seemed acid-precipitable, and consequently, seemed good candidates for the formation of acid yoghurt-type gels.…”
Section: Introductionmentioning
confidence: 99%